2016
DOI: 10.1103/physrevb.93.081405
|View full text |Cite
|
Sign up to set email alerts
|

Gap plasmonics of silver nanocube dimers

Abstract: We theoretically investigate gap plasmons for two silver nanocubes coupled through a molecular tunnel junction. In absence of tunneling, the red-shift of the bonding mode saturates with decreasing gap distance. Tunneling at small gap distances leads to a damping and slight blue-shift of the bonding mode, but no low-energy charge transfer plasmon mode appears in the spectra. This finding is in stark contrast to recent work of Tan et al. [Science 343, 1496[Science 343, (2014 [1,[3][4][5][6]. Molecular tunnel … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 28 publications
5
47
0
Order By: Relevance
“…This intriguing combination of molecular electronics with plasmonics was shown by Nijhuis' group who observed, using EELS, a charge transfer plasmon up to a separation of 1.3 nm for silver nanocubes functionalised with a monolayer of self-assembled molecules (SAMs) [139]. They found that the frequency of the CTP was dependent on the type of bridging molecule, for instance the size of the molecules HOMO-LUMO gap will dictate the tunnelling rate (we take this oportunity to point out that there has been some dispute of their intepretation of the experimental results regarding the CTP using the quantum corrected model [70]). This opens up the possibility of new biosensors that use changes in the tunnelling current to detect chemical concentrations and processes, for instance Benz et al have shown that difference of a thiol group (which allows the formation of a covalent bond to gold and hence can allow charge transfer) between biphenyl-4-thiol and biphenyl-4,4'-dithiol results in a shift of the coupled plasmon mode depending on the mole fraction of the two molecules [11].…”
Section: A Comparison Of Models: Dimer Systemsmentioning
confidence: 99%
“…This intriguing combination of molecular electronics with plasmonics was shown by Nijhuis' group who observed, using EELS, a charge transfer plasmon up to a separation of 1.3 nm for silver nanocubes functionalised with a monolayer of self-assembled molecules (SAMs) [139]. They found that the frequency of the CTP was dependent on the type of bridging molecule, for instance the size of the molecules HOMO-LUMO gap will dictate the tunnelling rate (we take this oportunity to point out that there has been some dispute of their intepretation of the experimental results regarding the CTP using the quantum corrected model [70]). This opens up the possibility of new biosensors that use changes in the tunnelling current to detect chemical concentrations and processes, for instance Benz et al have shown that difference of a thiol group (which allows the formation of a covalent bond to gold and hence can allow charge transfer) between biphenyl-4-thiol and biphenyl-4,4'-dithiol results in a shift of the coupled plasmon mode depending on the mole fraction of the two molecules [11].…”
Section: A Comparison Of Models: Dimer Systemsmentioning
confidence: 99%
“…The MNPBEM code developed by Hohenester and Trügler [89][90][91], which in recent years has been extensively used for the simulation of plasmonic nanoparticles [92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108], is used for these simulations. Further details can be found in Sec.…”
Section: Numerical Methods and Theorymentioning
confidence: 99%
“…As mentioned before, the gap conductivity mainly acts as a trigger for the appearence of the CTP peak [13,41], however, the precise σ t value is of only minor importance. Other quantities, such as the amount of charge transferred across the gap, could be influenced more strongly by σ t .…”
Section: Discussionmentioning
confidence: 99%
“…This is finding is in accordance to Refs. [13,41] where it was shown that σ t mainly triggeres the emergence of the CTP: below a critical value the CTP peak is absent, above the critical value the peak appears but its spectral position and shape is not substantially influenced by the precise magnitude of σ t .…”
Section: B Dft Tunnel Conductivitymentioning
confidence: 99%
See 1 more Smart Citation